Priming constraint-induced movement therapy with intermittent theta burst stimulation to enhance upper extremity recovery in patients with stroke: protocol for a randomized controlled study - Kolbaşı, Esma Nur; Ersöz Hüseyinsinoğlu, Burcu; Özdemir, Zeynep; Bayraktaroğlu, Zübeyir; Soysal, Aysun (My University, 2024)
Background: The treatments based on motor control and motor learning principles have gained popularity in the last 20 years, as well as non-invasive brain stimulations that enhance neuroplastic changes after stroke. However, the effect of intermittent theta burst stimulation (iTBS) in addition to evidence-based, intensive neurorehabilitation approaches such as modified constraint-induced movement therapy (mCIMT) is yet to be investigated. Aim: We aim to establish a protocol for a randomized controlled study investigating the efficiency of mCIMT primed with iTBS after stroke. Methods: In this randomized controlled, single-blind study, patients with stroke (N = 17) will be divided into 3 groups: (a) mCIMT + real iTBS, (b) mCIMT + sham iTBS, and (c) mCIMT alone. 600-pulse iTBS will be delivered to the primary motor cortex on the ipsilesional hemisphere, and then, patients will receive mCIMT for 1 h/session, 3 sessions/week for 5 weeks. Upper extremity recovery will be assessed with Fugl-Meyer Test-Upper Extremity and Wolf Motor Function Test. Electrophysiological assessments, such as Motor-Evoked Potentials, Resting Motor Threshold, Short-Intracortical Inhibition, and Intracortical Facilitation, will also be included. Conclusions: In this study, a protocol of an ongoing intervention study investigating the effectiveness of iTBS on ipsilesional M1 prior to the mCIMT in patients with stroke is proposed. This will be the first study to research priming mCIMT with iTBS and it may have the potential to reveal the true effect of the iTBS when it is added to the high-quality neurorehabilitation approaches. Trial registration: Trial registration number: NCT05308667.
Keywords: Cerebrovascular Accident; Neurological Rehabilitation; Transcranial Magnetic Stimulation; Upper Extremity